Spatialities of cultural landscapes: towards a unified vision of Spanish practices within the European Landscape Convention. Issue 9 (1st September 2020) - de la O Cabrera, Manuel Rodrigo; Marine, Nicolas; Escudero, David
ABSTRACT: Inspired by the European Landscape Convention, landscape conservation policies in European countries are increasingly becoming connected to cultural heritage policies. In some European countries such as Spain, the vision of the ELC has been enriched with that of the guidelines on the inclusion of Cultural Landscapes on the World Heritage List. The Spanish National Cultural Landscape Plan, an instrument for the implementation of the ELC promoted by the Spanish Institute of Cultural Heritage, expressly states that its definition of cultural landscape should be based on the definition of the UNESCO World Heritage Convention, but incorporating the ELC. However, this confluence is ultimately reflected in confronting guidelines. This study deepens this duality of the concept of cultural landscape, explores its conflicting spatial implications, and discusses its use in Spanish regional instruments. Through the statistical study of a sample of Spanish cultural landscapes, our study recognizes the need for guidelines for the identification of landscapes of special interest, especially if they are to be converted into cultural properties afterwards. Although the study cannot provide a method that solves the problem of the spatial dimensions of the landscape without major concessions, it has provided a classification of the dominant typology.